Pediatric Pathology Fellowship Recruitment—Report of a Survey Conducted by the Fellowship Committee of the Society for Pediatric Pathology. (May 2018) - Singh, Vivekanand; Eldin, Karen; Timmons, Charles; Bush, Jonathan; Rabah, Raja
Pediatric pathology (PP) is a subspecialty of pathology encompassing disease states during human development from the fetus to the young adult. Despite the existence of ACGME-accredited fellowship programs and opportunity for pediatric pathology subspecialty board certification, many pediatric pathology fellowship positions remain unfilled in North America. We sought to understand the difficulties in recruitment to the PP training programs by conducting a survey. A 3-pronged survey targeting pathology residents (PR), PP fellows and recent fellowship graduates (F&G), and PP training programs was conducted. Three separate questionnaires were prepared, one for each group; and administered online via SurveyMonkey. There were 175 responses to PR survey, 29 to F&G and 19 to programs survey. The results of the PR and F&G survey revealed that trainees select a subspecialty early in their residency training, primarily based on their interest, followed by prospects of employment. Nearly half of resident respondents had discounted pediatric pathology subspecialty training without prior exposure to the specialty. Senior residents and faculty members were reported as the main source for fellowship information for residents choosing subspecialty training and the choice of the training program was mostly dictated by geographic location. Most fellow recruits are racially diverse, female, and American medical graduates. Pathology residents decide on subspecialty training based on their interest; however, many are not exposed to pediatric pathology early on in training. The survey results suggest that existing PP fellowship positions likely will continue to exceed demand for subspecialty training. The results of the study could aid in developing strategies to boost recruitment to PP.